Tuberculosis Lymphoedema Cutis - Gangopadhyay Asok Kumar (Wolters Kluwer Medknow Publications, 2001)
Lymphoedema following cutaneous tuberculosis is a rare occurrence. A case of elephantiasis of leg following lupus vulgaris is presented. It can still be seen in rural India in untreated advanced cutaneous tuberculosis.